Characterization of primary, secondary and tertiary {202¯1}<1¯014> successive internal twins in the D019 ordered hexagonal α2-Ti3Al phase. (1st January 2022) - Song, Lin; Appel, Fritz; Pyczak, Florian; He, Zhanbing; Lin, Junpin; Zhang, Tiebang
Abstract: Due to the lack of independent slip systems and the difficulty in mechanical twinning, D019 ordered α2 -Ti3 Al phase is known to be of substantial mechanical anisotropy, which partly accounts for the low ductility of two-phase (α2 +γ) TiAl alloys. However, recent studies have shown that in Al-rich α2 phase compression deformation twins can be activated, which could be beneficial for the ductility of the alloys. In the present study, for the first time, we have revealed a novel internal twinning mechanism of α2 phase in a TiAl alloy deformed at high temperature. Three twin generations of a common type {20 2 ¯ 1}< 1 ¯ 014> were revealed: Secondary twins formed within the primary twin, and tertiary twins formed in the secondary twin. It is important to note that this internal twin structure can only be observed in the <2 1 ¯ 1 ¯ 6> direction but not the commonly used <11 2 ¯ 0> direction. The shear plane P of all twin variants is of type {1 2 ¯ 10}. Due to the variation of the twinning elements between the twin variants, the twinning shear is blunted. The interfaces between the twin variants are characterized by high-resolution electron microscopy. Special attention was paid to the structure of the coherent and incoherent twin boundaries. The effect of chemical ordering is discussed. Our results also shed light on the complex twinning mechanisms in hexagonal structures. Graphical abstract: Image, graphical abstract